*ABA in stem-allomorphy and the emptiness of the nominative. Issue 1 (19th January 2018) - McFadden, Thomas
Abstract : In this paper I examine patterns of irregular allomorphy in nominal stems sensitive to case in a number of nominative-accusative languages. I will argue that the data surveyed reveal a certain regularity in the distribution of irregularity across the cases in that they conform to what I call the Nominative Stem-Allomorphy Generalization. One irregular stem form is always found in the nominative (and in other cases that may be systematically syncretic with it), with all other cases sharing a single other stem form. I will show that this subsumes a clear instance of a *ABA pattern, and in fact is even more restrictive, as it also shows *ABC and (qualified) *AAB. I will situate these findings relative to recent work on *ABA patterns and on case-sensitive irregularity in noun and pronoun suppletion, and then will build on that prior work to propose an account for the generalization in terms of a structured representation of nouns and case categories interacting with locality conditions on allomorphy.